2016
DOI: 10.1073/pnas.1522054113
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting of the transcription factor Mohawk in rats causes heterotopic ossification of Achilles tendon via failed tenogenesis

Abstract: Cell-based or pharmacological approaches for promoting tendon repair are currently not available because the molecular mechanisms of tendon development and healing are not well understood. Although analysis of knockout mice provides many critical insights, small animals such as mice have some limitations. In particular, precise physiological examination for mechanical load and the ability to obtain a sufficient number of primary tendon cells for molecular biology studies are challenging using mice. Here, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 49 publications
11
121
1
1
Order By: Relevance
“…The results showed that iPSC-derived SYN and human primary tenocytes upregulated SYN-related markers in response to mechanical stress, consistent with previous reports (Fig. 4H) (Suzuki et al, 2016; Yang et al, 2004). These data demonstrate one aspect of the function of iPSC-derived SYNs.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that iPSC-derived SYN and human primary tenocytes upregulated SYN-related markers in response to mechanical stress, consistent with previous reports (Fig. 4H) (Suzuki et al, 2016; Yang et al, 2004). These data demonstrate one aspect of the function of iPSC-derived SYNs.…”
Section: Resultssupporting
confidence: 92%
“…Inflammation can also trigger heterotopic endochondral ossification, as established by several studies of traumatic or neurogenic injuries and congenital diseases383940. In addition, a recent study showed that the tendon transcription factor Mkx may also function to inhibit chondrogenic differentiation in tenocytes;41 our study showed downregulation of Mkx expression after adult tendon injury, which may permit cartilage differentiation at the expense of tenogenesis. Although our lineage tracing results showed a clear contribution of Scx lin tenocytes to ectopic cartilage, we also observed a number of non-labeled cells.…”
Section: Discussionsupporting
confidence: 67%
“…The transcription factor mohawk homeobox (Mkx), a member of the three-amino-acid loop extension (TALE) superclass of atypical homeobox genes, is expressed in the embryonic progenitor cell populations of the cartilage, skeletal muscle, tendons and bones, in addition to the tips of the ureteric buds in the metanephric kidneys and the testis cords of the male gonad testis in the mouse embryo (Anderson et al, 2006). Additionally, Mkx plays a crucial role in tendon maturation by regulating the expression of type I collagen (Ito et al, 2010;Liu et al, 2010;Nakamichi et al, 2016;Onizuka et al, 2014;Suzuki et al, 2016). However, the significance of Mkx in the PDL has never been explored.…”
Section: Introductionmentioning
confidence: 99%